On the Solutions of Some Boundary Value Problems for Integro-differential Inclusions of Fractional Order - Cernea, Aurelian (Journal of Applied Nonlinear Dynamics, 2026)
We study the existence of solutions for fractional integro-differential inclusions with nonlocal boundary conditions and with multi-order fractional integral conditions. We establish Filippov type existence results in the case of nonconvex set-valued maps.